Paper 05: The Role of the Long Head of the Biceps Tendon in Posterior Shoulder Stabilization during Forward Flexion. Issue 7 (30th July 2022) - Rauck, Ryan; Jahandar, Amir; Kontaxis, Andreas; Dines, David; Warren, Russell; Gulotta, Lawrence; Taylor, Samuel
Objectives: The incidence of long head of the biceps tendon (LHBT) procedures is increasing, yet the role of the LHBT in glenohumeral stability is not fully understood. People lift most objects in the sagittal plane with forward flexion, which stresses the posterior aspect of the unconstrained glenohumeral joint. Determining the mechanism by which the shoulder maintains stability with functional motions is important to understanding the pathoanatomy of degenerative shoulders. We hypothesize that the LHBT resists posterior translation of the humeral head (HH) during forward flexion by tensioning the posterior capsuloligamentous complex. Methods: Ten fresh-frozen cadaveric shoulders were tested using an established shoulder simulator, which loads the rotator cuff, deltoid and LHB tendons through a system of pulleys and weights. A motion tracking system recorded glenohumeral translations with an accuracy of ±0.2mm. In each subject, the scapula was fixed and the humerus was tested in 6 positions: 30 and 60 degrees of glenohumeral forward flexion at i) maximum internal rotation (IR), ii) neutral rotation and iii) maximum external rotation (ER) (Figure 1). The deltoid was loaded with 100N, and the infraspinatus and subscapularis were loaded with 22N each. The difference in glenohumeral translation was calculated at each position comparing the LHBT loaded with 45N or unloaded. Results: When comparing the two states of LHBT loading vs unloading, unloading the LHBT led to an overall increase in posterior and superior translation of the humeral head (Figure 2) in all tested positions (neutral, maximum internal rotation, maximum external rotation in both 30 and 60 degrees of forward flexion). At 30 degrees of glenohumeral forward flexion, unloading the LHBT increased HH posterior translation by 2.46mm (±0.92mm) (p<0.001), 1.71mm (±1.02mm) (p<0.001) and 1.02mm (±0.88mm) (p=0.014) at maximum ER, neutral rotation, and maximum IR, respectively (Figure 3). At 60 degrees of glenohumeral forward flexion, unloading the LHBT increased HH posterior translation by 2.77mm (±1.16mm) (p<0.001), 2.43mm (±1.56mm) (p<0.001) and 1.66mm (±1.42mm) (p<0.001) at maximum ER, neutral rotation and maximum IR, respectively (Figure 4). Unloading the LHBT led to more posterior translation at 60 degrees of glenohumeral forward flexion compared to 30 degrees (p=0.013). Conclusions: LHBT loading resists posterior translation of the humeral head during forward flexion. This data supports the role of the LHBT as a posterior stabilizer of the shoulder, specifically when a person is carrying objects in front of them. Biceps tenotomy or tenodesis may contribute to microinstability of the glenohumeral joint and shift contact pressure posteriorly. Further work is needed to determine if unloading the LHBT, as is done with biceps tenotomy or tenodesis, may eventually contribute to the posterior glenoid wear seen with osteoarthritis.